A Visual Programming Tool to Design Mixed and Virtual Reality Interactions - Loup, Guillaume; George, Sébastien; Marfisi, Iza; Serna, Audrey (International Journal of Virtual Reality, 2018)
Mixed and Virtual Reality (MVR) devices are now more accessible. However, developing MVR applications is still complex for the majority of developers, because it requires specific expertise. For the past few years, several packaged solutions offered to assist developers who are non-MVR experts. These solutions rarely offer full freedom to create specific interactions adapted to the context. We therefore propose a new MVR tool named MIREDGE (MIxed and virtual REality Development tool for Game Engine). Its interface allows visual programming of MVR interactions. This solution aims at allowing developers to capitalize, re- use, share and associate interaction algorithms. It also takes into account software and hardware compatibility in order to compose new algorithms. The specific architecture of MIREDGE provides opportunities for MVR and non-MVR developers to collaborate to meet a common need: writing efficient MVR interaction algorithms. MIREDGE Editor was evaluated by 31 MVR and non-MVR developers. Results shows that MIREDGE Editor seems effective and efficient particularly for non-MVR developers.